From words to worlds: Generative reconstruction of The Alchemist narratives - Tan, Franseno Pujianto (Department of Architecture Faculty of Engineering Universitas Indonesia, 2024)
This paper explores the creative translation of narratives into atmospheric qualities of space using artificial intelligence (AI). The study transforms the textual descriptions of events based on the notable works of Paulo Coelho's The Alchemist into generative architectural representations. Exploration of prompts in text-to-image generative technologies is still defined by the description of forms and context instead of based on events. The study argues that utilising stories of events as prompts creates possibilities for a more enriching and evocative visual of architecture. This study utilises the Microsoft Bing Image Generator DALL-E 3 to generate images based on prompts derived from key events of The Alchemist. Nine particular events of The Alchemist novel are transformed into images, which are further transformed into AI-generated prompts. The study follows by regenerating the prompts into another set of images. The resulting AI-generated images reveal the potential of AI in creating architectural spaces that embody the atmospheric qualities of The Alchemist narratives, with varying degrees of details and nuances of the narrative events. Through annotating the generated forms, the contrast of lights, and the materiality of the generated images, the study creatively reconstructs the atmospheric qualities of The Alchemist events. In doing so, the study blurs the lines between textual and spatial storytelling, empowering the craft of meaningful and impactful spaces through the power of narrative. This paper highlights the potential of AI not just as a tool for visualisation but also as a catalyst for innovative and creative exploration in the design field.